Knowledge Management and the Informal Sector: a Qualitative Review - Isaac Onyeyirichukwu Chukwuma; Uzoma Ogochukwu Okonkwo (International Journal of Asian Business and Management, 2023)
The exploration of knowledge management and its influence on the informal sector has become a topical interest to industries and academia. Nonetheless, the current deficiency in literature to reveal empirical association between knowledge management and the informal sector is a critical gap this study sought to reduce. Hence, this study specifically examines the interrelationship between knowledge management and the informal sector. The study employed a qualitative descriptive method in analyzing relevant related studies and was anchored on the absorptive capacity theory. The study concludes that the analysis of knowledge management revealed its growing significance at a rapid trajectory that transcends the informal sector; the increasing need and demand for strategic activation, engagement, and execution of knowledge management activities have become much pronounced and invaluable to the sustainable posterity of the affairs of the informal sector. The study also made postulation on the prospect of the association between knowledge management and the informal sector